Amenability of an Agrobacterium tumefaciens-mediated shoot apical meristem-targeted in planta transformation strategy in Mango (Mangifera indica L.). Issue 1 (31st December 2022) - Pandey, Kuldeep; Karthik, Kesiraju; Singh, Sanjay Kumar; Vinod,; Sreevathsa, Rohini; Srivastav, Manish
ABSTRACT: Mango ( Mangifera indica L.) is one of the most popular tropical fruits in the world owing to its rich taste, flavor, color, production volume and diverse end usage. Conventional mango breeding practices are unable to withstand the demand for improved varieties as it is time consuming and requires heavy investment. However, problems associated with traditional plant breeding can be curtailed through genetic transformation. Nevertheless, major limitation of transgenic development has been its recalcitrant nature toward tissue culture practices involving latent microbial infection, phenol exudation, etc. This opens wide scope for tissue culture-independent in planta transformation approaches These strategies have proved to be easy to execute and cost effective in producing large number of transformants. One such apical meristem targeted in planta approach was successfully exploited to demonstrate its utility in transforming a tree species. Mango variety Amrapali was transformed with two visual marker gene vectors GFP::hptII in pCAMBIA1302 and GUS::nptII in pCAMBIA2301 individually, to demonstrate its amenability. Preliminary confirmations identified 65.0% of GFP and 57.14% of GUS plants to be transformed. Further, molecular characterization of these primary transformants demonstrated transgene integration at genomic and transcript level in some of the plants. This established protocol holds good for functional gene validation and knock in/out studies and aid in mango improvement programs.